EFFECTIVENESS AND SAFETY OF SOFOSBUVIR AND VELPATASVIR IN HEMODIALYSIS PATIENTS SUFFERING WITH HEPATITIS C INFECTION - Mehmood, Yasir; Muhammad Imran Ashraf; Khadija Mastoor; Adnan Afzal; Zafar Latif Awan (Journal of University Medical & Dental College, 2021)
BACKGROUND & OBJECTIVE: There is scantiness of evidence-based knowledge of anti-viral therapy with sofosbuvir (SOF) and velpatasvir (VLP) in patients on maintenance haemodialysis. This report is an attempt to rationalise the safety and effectiveness of SOF and VLP in haemodialysis patients in Pakistan. METHODOLOGY: Twenty treatment-naïve patients were incorporated in this study. Patients on maintenance haemodialysis are being administered SOF and VLP. Before initiation of treatment, all necessary investigations such as viral load, liver fibro scan, genotyping and upper GI endoscopy were made. Patients received 400 mg/day and 100 mg/day dose of SOF and VLP, respectively. RESULTS: Mean age was 25 to 53 years; 30% were male and 70% were female as categorized. No one of these has clinical affirmation of progression of cirrhosis. The most prevalent genotype was genotype 4 that was found in 45% of cases and the second most evident was genotype 1 in 25% of cases and genotype 5 in 30% of cases. Time span of antiviral therapy was 12 weeks. CONCLUSION: SOF and VLP based direct antiviral agents were effectual, puissant and were aptly tolerated in patients on MHD. This drug combination was well tolerated in haemodialysis patients. Not a single patient discontinued this combination therapy due to severe complications.